2004
DOI: 10.1562/0031-8655(2004)79<40:mtados>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Anatomical Distribution of Sunlight¶‡

Abstract: One of the major technical challenges in calculating solar irradiance on the human form has been the complexity of the surface geometry (i.e. the surface-normal vis-a-vis the incident radiation). Over 80% of skin cancers occur on the face, head, neck and back of the hands. The quantification, as well as the mapping of the anatomical distribution of solar radiation on the human form, is essential if we are to study the etiology of skin cancers or cataracts or immune system suppression. Using advances in compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
(5 reference statements)
0
30
0
Order By: Relevance
“…We consider the irradiance ratio for standing position at 45° of solar elevation angle, with different coefficients weighted on azimuth angle and posture prevalence [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…We consider the irradiance ratio for standing position at 45° of solar elevation angle, with different coefficients weighted on azimuth angle and posture prevalence [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, a linear association between lip cancer incidence and latitude was not observed in this study, nor is it observed in the general Australian population (32). One explanation for this apparent incongruence with other indices of exposure to solar UV radiation is that the anatomic positioning of the lips makes them particularly susceptible to irradiation when the sun is low in the sky (33).…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, in which the head is tilted towards the sun, spectacle lenses provide specifically efficient protective effects. Due to the plurality of factors influencing individual UV exposure, strong efforts have been made to estimate UV-exposure from UV dose readings at different inclinations as well as inclination estimations of human body surface [41][42][43][44]. Estimates of ocular UV exposure from general UV exposure range from 2 % -23 % [24,45], indicating a significant impact on the sensitive ocular tissue and surrounding skin.…”
Section: Discussionmentioning
confidence: 99%